Збереження та розвиток національних традицій у хореографічних колективах української діаспори - Островська, Каріна Володимирівна (ХДАК, 2018)
Досліджено та обґрунтовано, що український народний танець нині популярний не тільки в Україні, а й у багатьох країнах світу. За кордоном існує немало українських танцювальних ансамблів, які зберігають та популяризують танцювальне мистецтво України. Відзначено праці, де досліджено побут перших українських переселенців у Канаді кінця XIX ст. У репертуарі багатьох колективів широко представлена хореографія різних регіонів України, від слобожанщини до Закарпаття. Український народний танець у колективах української діаспори зберіг самобутність, відроджуючи характерні особливості української народної культури. Українське мистецтво є не лише консервативним і традиційним, воно живе й нове, нині є складовою загальної світової культури.

There are many Ukrainian dance companies abroad that maintain and popularize the dance art of Ukraine. Due to their wide creative work, the rarest standards of folklore are maintained, glorifying not only the Ukrainian choreography art, and also the Ukrainian culture with its unique history, ceremony, traditions and way of life. The study has confirmed that most dancing companies of the Ukrainian Diaspora are amateur ones; nevertheless they have an impact on forming the Ukrainian culture in some countries. The choreography of different regions of Ukraine, from Slobozhanshchina to Transcarpathia, is widely represented in the repertoire of many companies. Ukrainian folk dance in the companies of the Ukrainian Diaspora has maintained its identity, reviving the characteristic features of Ukrainian folk culture. The Ukrainian Diaspora has plenty of dancing companies, which maintain the standards of dancing folklore on the modern stage, working hard to improve the skills and professional level. Due to these companies Ukrainian dancing art becomes more popular all over the world. Ukrainian art is not only conservative and traditional, it is alive and new, nowadays it is an integral part of a common world culture.
Keywords: хореографія народна; хореографічні колективи; український народний танець; Ukrainian folk dance